A proposed framework for the curriculum of Islamic education : implications on the curricula of Islamic religious higher education institutions in Kerala, India - Vazhathodi, Shafeeq Hussain (Institute of Education, International Islamic University Malaysia, 2011)
This study attempts to trace the foundations of the Islamic education and its curriculum in an effort to revive the curricula of the Islamic Religious Higher education (IRHE) system prevalent in India. It is undertaken in the context of the persistent pleas from various intellectuals and educators to revitalize the system, especially in the light of contemporary challenges to Islam and Muslims on various fronts. Hence, firstly, the study explores various fundamental elements and structures of the Islamic Worldview. Then, the study establishes the relevance of and coherency among these elements by indicating how they are represented in various Islamic codes of conduct (Sharī'ah), and Sharī'ah principles ('usūl) and objectives (maqāsid). Secondly, the study explores what these essential elements imply to the foundations of the curriculum of Islamic education, its fields of exposition as well as its pedagogical focus. Accordingly, the researcher proposes a 'basic' curriculum framework for Islamic education. Further, the researcher identifies the role of IRHE institutions and the 'ulamā' produced in them in providing proactive and visionary leadership. Lastly, the study explores the implications of the framework on the IRHE institutions in Kerala and their curricula, educational intents, contents, pedagogy and the methods of evaluation. While undertaking these exercises, the study primarily uses a philosophical and analytical approach. Various deliberations carried out using these methods have proved that the Islamic education system, although theological in essence, is practical and pragmatic in spirit. In fact, the three essential Islamic elements of faith, knowledge and value, make sense only within the human and civilizational domains. These five key structures of the Islamic Worldview constitute the theological/spiritual, intellectual/psychic, moral, physical/social and civilizational foundations and dimensions of the Islamic education curriculum. They are unified by the core concept of faith. Together, they impinge on the educational intents, contents, pedagogy and the methods of evaluation.